Matching to share risk - Pierre-André Chiappori; Philip J. Reny (Theoretical Economics, 2016)
We consider a matching model in which individuals belonging to two populations (“ males” and “ females” ) can match to share their exogenous income risk. Within each population, individuals can be ranked by risk aversion in the Arrow-Pratt sense. The model permits non transferable utility, a context in which few general results have previously been derived. We show that in this framework a stable matching always exists, it is generically unique, and it is negatively assortative: for any two matched couples, the more risk averse male is matched with the less risk averse female.
Keywords: D00; C78; 330; Negatively assortative matching; risk-sharing; stable match